Criminal Liability in Case of Acute Kidney Failure in Indonesian Health Legal Perspective - Raihanah, Ayu Iasha; Napitupulu, Eunike Agalia (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2023)
Cases of Atypical Progressive Acute Kidney Injury (AKI) have caused hundreds of children to die mysteriously, which has caused anxiety for all Indonesian people. The Ministry of Health noted that the number of cases of acute kidney failure as of November 7, 2022, had reached 324 cases, with a death rate of 195 children who had died. The high mortality rate due to acute kidney disease is thought to be caused by poisoning with the compounds Ethylene Glycol (EG) and Diethylene Glycol (DEG), which are commonly used as solvents in liquid medicines. It is necessary to know in advance whether there is causality between the act and intention, whether it is true that the active ingredient is the main cause of kidney failure, and the form of accountability from the parties involved as contained in Article 196 of Law Number 36 of 2009 concerning Health. In this case of acute kidney failure, it was found that several potential negligences led to death in this case, starting from the licensing process to drug control, maladministration by the Ministry of Health, pre-post market supervision regulations, and National Agency of Drug and Food Control’s (BPOM) strategy in preventing unwanted events.